Concepts for the design and evaluation of change-oriented research - Belcher, B. (Research Publishing International, 2021)
Research funding bodies, and society in general, have high expectations for research to contribute solutions that have positive societal and environmental impact. This desire to increase societal benefits has prompted an evolution in how research is conducted, and a corresponding need for appropriate research evaluation tools and approaches. The Sustainability Research Effectiveness Program, led by Professor Brian Belcher at Royal Roads University, has responded to this need by developing a Transdisciplinary Research Quality Assessment Framework to evaluate research design and implementation and a theory-based evaluation approach to assess research contributions to outcomes and impacts.